Konsep Pendidikan Pluralisme dan Pendidikan Karakter Islam Perspektif Abdurrahman Wahid (Gus Dur) Serta Relevansinya di Era Revolusi Industri 5.0 - Mohammad Faizal Agung; Hery Noer Aly (Al-Bahtsu: Jurnal Penelitian Pendidikan Islam, 2021)
This research is titled "The Concept of Pluralism and Islamic Character Education from the Perspective of Abdurrahman Wahid (Gus Dur) and Its Relevance in the Era of Industrial Revolution 5.0". Abdurrahman Wahid, better known as Gus Dur, is a highly influential figure in Islamic thought in Indonesia, particularly in the areas of pluralism and character education. This study aims to deeply examine the concepts of pluralism and character education according to Gus Dur's views, and to assess their relevance in the context of the Industrial Revolution 5.0 era. The research method used is a literature review with a qualitative descriptive approach. Data were obtained from various sources such as books, articles, and Gus Dur's speeches, as well as literature related to character education and the Industrial Revolution 5.0. The results of the study show that Gus Dur's concept of pluralism emphasizes the importance of mutual respect and tolerance between religious communities and social groups. Character education, according to Gus Dur, is an effort to shape individuals with noble character, integrity, and high social awareness. In the context of the Industrial Revolution 5.0, where technology and digitalization are rapidly advancing, the values of pluralism and character education promoted by Gus Dur are increasingly relevant. This era demands high adaptability and openness to diversity to create harmony amidst rapid changes. This study concludes that the implementation of Gus Dur's concept of pluralism and Islamic character education can make a significant contribution to forming an inclusive and civilized society in the era of Industrial Revolution 5.0.